Threatened miscarriage: evaluation and management - Sotiriadis, Alexandros; Papatheodorou, Stefania; Makrydimas, George (My University, 2004)
Threatened miscarriage—vaginal bleeding before 20 gestational weeks—is the commonest complication in pregnancy, occurring in about a fifth of cases.w1 Miscarriage is 2.6 times as likely,1 and 17% of cases are expected to present complications later in pregnancy.2 Although general practitioners and gynaecologists often see this condition, management of threatened miscarriage is mostly empirical. Bed rest is routinely recommended, and about a third of women presenting with threatened miscarriage are prescribed drugs.w2 However, two thirds of the general practitioners recommending this do not believe it affects outcome.3 In this review, we present available evidence on the initial evaluation and management of threatened miscarriage, focusing mainly on the first trimester of pregnancy and primary healthcare settings.
Keywords: Pregnancy; Vaginal bleeding; Gestational sac; Anti-Rh D